KANDUNGAN MINYAK, HUBUNGAN KEKERABATAN DAN POTENSI BIODIESEL DARI KEPUH (Serculia foetida L.) DI KABUPATEN BADUNG, KOTA DENPASAR DAN ROTE (NTT) - Ndolu, Midel Delfi Wehelmina; Arpiwi, Ni Luh; Suriani, Ni Luh (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018)DO - 10.24843/metamorfosa.2018.v05.i01.p11, 2018)
Kepuh ( Sterculia foetida L.) is non-food plant produces seed oil that can be used as  a biodiesel feedstock. This study aims to determine the characteristics of seeds, oil content, kinship relationship and quality of biodiesel from Sterculia foetidas seed in Badung, Denpasar and Rote. The research was conducted on December 2016 - May 2017. The method used was observation of seed characteristics, analyzing oil content and biodiesel quality from oil Sterculia foetida ’ s . The highest oil content was obtained from Badung regency and Denpasar  that was Monang-Maning 1 =  41.13%, while the lowest of Rote in Oemasi was 14.80%. The kinship relationship between seed characteristics and oil content formed 2 groups with a similarity index of 93.5%. The quality of biodiesel in Badung and Denpasar with  acid number of 0.34 mg-KOH/ g and Rote that was 0.44 mg-KOH/g, iodine number in Badung and Denpasar were 44.41 and Rote was 48.53. Saponification number in Badung and Denpasar were 187.93 and Rote was 194.94, cetane number in Badung and Denpasar were 64.02 and Rote was 61,92. Water content in Badung, Denpasar and Rote was 0,2 respectively, and viscosity in Badung and Denpasar were 12.23 cSt and Rote  was 9.22 cSt. The quality of biodiesel obtained mostly fulfilled the provisions of SNI 2015, except viscosity.